Peningkatan SDM Menuju Kemandirian UMKM Melalui Kualitas Pendidikan dalam Mewujudkan Tujuan Pembangunan yang Berkelanjutan (Suistanaible Development Goals) di Desa Ciwalat Kec. Pabuaran, Kab. Sukabumi - Juhaeri, Juhaeri; Wulandari, Kintan Candra; Kustini, Kustini; Hutagalung, Debora; Fudri, Acep; Mukrodi, Mukrodi; Sewaka, Sewaka (Jurnal PKM Manajemen Bisnis, 2024)
Increasing Human Resources Towards MSME Independence through Quality Education in Realizing Sustainable Development Goals in Ciwalat Village, District. Pabuaran, Kab. Sukabumi. This service was carried out on Sunday, June 2 2024, which was attended by 20 students and 6 supervisors from Pamulang University. The general aim of this community service activity is to socialize that the way to achieve MSME independence and improve human resources is through quality education so that sustainable development can be achieved in Ciwalat Village. The methods used are survey methods and direct delivery of material as well as simulations and discussions regarding management, HR management, marketing of MSME products. This service activity succeeded in providing understanding to the community, especially the importance of quality education in improving human resources and developing MSMEs in an effort towards sustainable development.